OTOTOXIC EFFECTS OF HIDROXYCHLOROQUINE: A SYSTEMATIC REVIEW - Gonçalves , Laura Faustino (2020)
Objective: To present scientific evidence based on a systematic literature review (PRISMA), in order to systematize evidence on the ototoxic effects of hydroxychloroquine (HCQ). Methods: For the selection of studies, the combination based on the Medical Subject Heading Terms (MeSH) was used. The Medline (Pubmed), LILACS, SciELO and BIREME databases were used. The search period for the articles ranged from January 2010 to May 2020, without language and localization restrictions. Results: 148 articles with potential for inclusion were retrieved, with two articles answering the guiding question that consisted of seeking evidence of the ototoxic effects of hydroxychloroquine. These studies scored 11 in the modified protocol by Pithon et al, to assess their quality. Conclusion: Studies have reported a possible ototoxicity of HCQ. Audio-vestibular changes such as hearing loss, peripheral vestibular syndrome and tinnitus were observed in patients undergoing HCQ. The improvement in audiological exams, as well as the regression of the vestibular syndrome after the interruption of HCQ treatment, are strong arguments in favor of the ototoxicity caused by this medication. However, there are still disagreements about the relationship of ototoxic effects and the use of HCQ.